Method Matters Effects of Explicit Versus Implicit Social Comparison on Activation, Behavior , and Self-Views. (article). - Stapel, Diederik A.
The authors investigated the impact of explicit versus implicit social comparisons. Simply being primed with a superior or inferior standard (implicit comparison) produced contrast as evidenced by accessibility of self-knowledge (Study 2), intellectual performance (Study 3), and self-ratings (Study 4), inconsistent with the standard. However, when participants were explicitly asked to compare, increased accessibility of a similarity focus (Study 1) and self-knowledge , behavioral performance, and self-ratings congruent with the standard were obtained more easily,indicative of assimilation. Explicit comparisons produced assimilation when the self was seen as mutable (rather than immutable; study 4), when behavioral consequences were measured immediately after the comparison (rather than later; study 3),and when the participants described (rather than ranked) their intelligence; (study 5). These findings support the interpretation comparison model. Implications for resolution of empirical inconsistencies in the social comparison literature are discussed. -- (from the athor).
Keywords: Psychology-Periodicals.